E-health empowers patients with ulcerative colitis: a randomised controlled trial of the web-guided 'Constant-care' approach. - SHUHAIBAR, MARY; O'MORAIN, COLM (My University, 2010)
Background: The natural history of ulcerative colitis requires continuous monitoring of medical treatment via frequent outpatient visits. The European health authorities' focus on e-health is increasing. Lack of easy access to inflammatory bowel disease (IBD) clinics, patients' education and understanding of the importance of early treatment at relapse is leading to poor compliance. To overcome these limitations a randomised control trial `Constant-care? was undertaken in Denmark and Ireland. Methods: 333 patients with mild/moderate ulcerative colitis and 5-aminosalicylate acid treatment were randomised to either a web-group receiving disease specific education and self-treatment via http://www.constant-care.dk or a control group continuing the usual care for 12 months. A historical control group was included to test the comparability with the control group. We investigated: feasibility of the approach, its influence on patients' compliance, knowledge, quality of life (QoL), disease outcomes, safety and health care costs. Results: 88% of the web patients preferred using the new approach. Adherence to 4 weeks of acute treatment was increased by 31% in Denmark and 44% in Ireland compared to the control groups. In Denmark IBD knowledge and QoL were significantly improved in web patients. Median relapse duration was 18 days (95% CI 10 to 21) in the web versus 77 days (95% CI 46 to 108) in the control group. The number of acute and routine visits to the outpatient clinic was lower in the web than in the control group, resulting in a saving of 189 euro/patient/year. No difference in the relapse frequency, hospitalisation, surgery or adverse events was observed. The historical control group was comparable with the control group. Conclusion: The new web-guided approach on http://www.constant-care.dk is feasible, safe and cost effective. It empowers patients with ulcerative colitis without increasing their morbidity and depression. It has yet to be shown whether this strategy can change the natural disease course of ulcerative colitis in the long term.
PUBLISHED
Keywords: Gastroenterology; ulcerative colitis; E-health